2019
DOI: 10.1080/1750984x.2019.1656276
|View full text |Cite
|
Sign up to set email alerts
|

Thinking through and designing qualitative research studies: a focused mapping review of 30 years of qualitative research in sport psychology

Abstract: Amid the increasing use of qualitative methods in the field of sport psychology, a number of researchers have initiated discussions about issues of rigour and quality in qualitative inquiry. Methodological coherence has been offered as an approach to strengthening qualitative inquiry by ensuring that the elements of qualitative research are appropriately aligned. This study presents a focused mapping review and synthesis of the methodological coherence of qualitative sport psychology research published in five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 23 publications
0
74
0
5
Order By: Relevance
“…It is important to recognise that qualitative research is situated on a continuum of diverse philosophical assumptions and may not necessarily be conducted from nonrealist ontological and subjectivist epistemological positions. Indeed, a recent review of 30 years of qualitative research reported that most commonly used implicit assumptions in SEP research stem from realism (Poucher et al, 2020). Some see ontological realism inevitably underpinning scientific epistemologies of positivism and postpositivism with the latter being a softer version of the former (e.g., Smith & Sparkes, 2016).…”
mentioning
confidence: 99%
“…It is important to recognise that qualitative research is situated on a continuum of diverse philosophical assumptions and may not necessarily be conducted from nonrealist ontological and subjectivist epistemological positions. Indeed, a recent review of 30 years of qualitative research reported that most commonly used implicit assumptions in SEP research stem from realism (Poucher et al, 2020). Some see ontological realism inevitably underpinning scientific epistemologies of positivism and postpositivism with the latter being a softer version of the former (e.g., Smith & Sparkes, 2016).…”
mentioning
confidence: 99%
“…Methodological coherence describes the 'congruence between the researcher's epistemological and ontological viewpoint, theoretical position/perspective, the methods, and so on' (Poucher et al, 2020). This article is derived from the qualitative research method (Schoonenboom & Johnson, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The rest of this paper is characterised by persuasive dialogue, yet some might portray it in some ways as a rhetorical discourse (Fisher, 1985); nonetheless, as this research implies limited replication, the procedure adopted is the quasi-narrative review (Poucher et al, 2019). A narrative review allows for the author's opinion to be used as the interpretative feature of the research (Merriam and Tisdale, 2016) as the researcher attempts to "personalise the research process in a way not easily achieved through quantitative designs, yet demands its own set of procedures and techniques".…”
Section: Scope and Literature 21 Scopementioning
confidence: 99%